KEWAJIBAN BALIK NAMA OLEH PEMBELI DALAM JUAL BELI TANAH BERDASARKAN PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH DI DESA WAJOK HILIR KECAMATAN JONGKAT KABUPATEN MEMPAWAH - NIM. A1011181206, PUTRI UTARI (Fakultas Hukum Universitas Tanjungpura, 2022)
Abstract The transfer of ownership of land that is often carried out in the community is through a buying and selling process. Based on Article 37 paragraph (1) Government Regulation Number 24 of 1997 concerning Land Registration states that